Time‐Resolved Evolution of the 3D Nanoporous Structure of Sintered Ag by X‐Ray Nanotomography: Role of the Interface with a Copper Substrate. Issue 1 (26th October 2021) - N'Tsouaglo, Kokouvi Happy; Milhet, Xavier; Colin, Jérôme; Signor, Loic; Nait-Ali, Azdine; Creus, Juan; Gueguen, Mikael; Gadaud, Pascal; Legros, Marc
Abstract : The evolution of the nanoporous structure of cylindrical sintered silver samples during high temperature aging, ranging from 200 to 350 °C for 350 min, is studied through in situ computed X‐ray tomography. Investigations are carried out for two types of specimens: pure sintered silver and specimens containing a silver‐copper interface. It is shown that the overall pore evolution is driven by the evolution of very few large ones. The smaller pores, although being more numerous, do not really evolve before being absorbed by the few bigger ones. In pure silver, pore evolution is driven by diffusion (Ostwald ripening) but the presence of an interface promotes faster growth kinetics until the aging time reaches a threshold value, after which a deviation from Ostwald ripening occurs. The transition is a function of the aging temperature. This behavior is associated with the competition between elastic relaxation and surface energy minimization. Abstract : Computed X‐ray nano‐tomography is used to monitor the evolution of the porous structure of sintered silver coated with copper. While the pore evolution follows Ostwald ripening, the presence of thermal stresses near the interfaces promotes faster growth kinetics until a deviation from Ostwald ripening occurs. This behavior is associated with the competition between thermal stresses relaxation and surface energy minimization.